Analysis of cephalosporins by hydrophilic interaction chromatography - Liu, Qiaoxia; Xu, Lingyan; Ke, Yanxiong; Jin, Yu; Zhang, Feifang; Liang, Xinmiao (Journal of pharmaceutical and biomedical analysis, 2011)
A simple hydrophilic interaction chromatography (HILIC) method was developed to analyze seven cephalosporins. These seven cephalosporins could be separated well on the Click β-CD column and Atlantis HILIC Silica column. The effects of buffer concentration and pH on the retention under HILIC mode were studied. Except cefepime hydrochloride ( 4), the retention of other six cephalosporins increased with increasing buffer concentration, while decreased with increasing pH. Different separation selectivities could be observed on the Click β-CD column and Atlantis HILIC Silica column, and changing pH also resulted in the changing of separation selectivity. The separations of cephalosporins by HILIC and reversed-phase high performance liquid chromatography (RP-HPLC) were compared, and the two separation modes had good orthogonality. In addition, cefotaxime sodium ( 1) and its degradation were separated well on the Click β-CD column, which indicated that the Click β-CD column by HILIC can be used for studying the stability of cephalosporins.